2020
DOI: 10.1038/s41598-020-68017-y
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-loaded iron oxide nanoparticles for glioblastoma therapy: a combinational approach for enhanced delivery of nanoparticles

Abstract: Although doxorubicin (DOX) is an effective anti-cancer drug with cytotoxicity in a variety of different tumors, its effectiveness in treating glioblastoma multiforme (GBM) is constrained by insufficient penetration across the blood-brain barrier (BBB). In this study, biocompatible magnetic iron oxide nanoparticles (IONPs) stabilized with trimethoxysilylpropyl-ethylenediamine triacetic acid (EDT) were developed as a carrier of DOX for GBM chemotherapy. The DOX-loaded EDT-IONPs (DOX-EDT-IONPs) released DOX withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(127 citation statements)
references
References 91 publications
6
121
0
Order By: Relevance
“…Therefore, our data confirm this finding and strengthens the theory of the lysosomal vulnerability of GSCs. Our results further suggest that PEI modification imparts a new, inherent property to nanoparticles in selective killing of GSCs without any additional anti-cancer drug treatment, which is contrary to recently reported drug based nanomedicinal approaches to eradicate GB [64][65][66][67]. We also demonstrated the potential of the PEI-MSNs to be directly delivered to GSCs via intranasal or intravenous administration for the successful eradication of GSCs in vivo.…”
Section: Pei-msns Cross the Neurovascular Unit In Vitro And In Vivomentioning
confidence: 46%
“…Therefore, our data confirm this finding and strengthens the theory of the lysosomal vulnerability of GSCs. Our results further suggest that PEI modification imparts a new, inherent property to nanoparticles in selective killing of GSCs without any additional anti-cancer drug treatment, which is contrary to recently reported drug based nanomedicinal approaches to eradicate GB [64][65][66][67]. We also demonstrated the potential of the PEI-MSNs to be directly delivered to GSCs via intranasal or intravenous administration for the successful eradication of GSCs in vivo.…”
Section: Pei-msns Cross the Neurovascular Unit In Vitro And In Vivomentioning
confidence: 46%
“…Furthermore, according to a recent study [ 26 ], bEnd.3 was found to have a higher lysosomal degradation activity than primary cells, therefore making it particularly suitable for studies involving biological permeation mechanisms such as transcytosis. For this reason, this model has recently been widely used to study the permeability of nanosystems through the BBB [ 27 , 28 , 29 ]. The paracellular pathway permeability to fluorescein ( Figure S4 ), the monolayer integrity, and adequate cell differentiation by the hematoxylin/eosin coloring and the fluorescence analysis (scanning laser confocal microscopy) ( Figure S5 ) were verified.…”
Section: Resultsmentioning
confidence: 99%
“…[245] Recent studies have also shown that CED treatments under the guidance of MRI or single photon emission computed tomography provide useful real-time feedback to the clinicians in monitoring the drug delivery process and to confirm adequacy of the drugs delivered to the tumor. [245][246][247][248][249] With recent advances in image-guided drug delivery, locoregional targeted chemotherapy will continue to grow and improve the mortality and morbidity of cancer patients. This method may be coupled with active and passive targeting strategies to reduce the influence of blood flow direction and diffusion gradients from the intravascular to the interstitial space.…”
Section: Locoregional Deliverymentioning
confidence: 99%
“…Locoregional chemotherapy. [244][245][246][247][248][249] active targeting moieties. [253] This phenomenon could prolong the circulation time of the drug and enables the delivery of anticancer agents to different tumor compartments, hence resulting in better therapeutic outcomes.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%